AB0686 Association between drug serum levels and disease activity in espondiloarthritis patients treated with golimumab. (15th June 2017) - Redondo, C; Martínez, A; Plasencia, C; Jochems, A; Pascual-Salcedo, D; Navarro-Compán, V; Bonilla, MG; Monjo, I; Balsa, A
Abstract : Background: Efficacy and safety of Golimumab (Glm) has been demonstrated for spondiloarthritis (SpA). Nonetheless, there is little data determining an association between an optimal drug levels concentration and the maintenance of a good control of disease activity. In Spa-Paz cohort we defined previously an optimal Glm levels concentration associated with a good clinical response. Objectives: To investigate the association between serum levels of Glm, based on the optimal concentration defined previously in Spa-Paz cohort, and disease activity in a larger cohort of SpA. Methods: Observational prospective SpA-Paz cohort study treated with Glm. Disease activity was measured by ASDAS and clinical improvement using Delta-ASDAS at baseline, 6 and 12 months of biologic therapy. ASDAS<2.1 was considered as low activity and clinically important improvement as Delta-ASDAS≥1.1. Drug levels were measured by ELISA at 6 and 12 months of therapy and classified in 3 groups based on the optimal concentration range previously defined in our cohort: Group 1:<0.7 mg/L, group 2: 0.7–1.4 mg/L, group 3: >1.4 mg/L. At 12 months we made a LOCF analysis to include patient data (11 patients) with less than 12 months of treatment. We used the software Graph-Pad Prism 6 for statistical analysis. Results: 46 patients of 79 with SpA treated with Glm were included in this study. The average age was 49 years old (age range 22–72 years old), 31 men (67%) and 15 women (33%). 22 patients (48%) were non-smokers and 13 (28%) active smokers. 25 (54%) were HLA-B27 positive. In total, 17 patients (37%) were classified in group 1, 16 (35%) in group 2 and 13 (28%) in group 3. At 12 months of therapy, most patients in low disease activity were in groups 2 and 3 but nevertheless, the majority of high disease activity patients were in group 3 (76% in groups 2 and 3 vs. 41% in group 1 with ASDAS<2.1; 24% in group 2 and 3 vs. 53% in group 1 with ASDAS≥2.1; p<0.0001). Likewise, clinical improvement was significantly higher in groups 2 and 3 patients (62% in groups 2 and 3 vs. 35% in group 1, p>0.0002). There were no differences in clinical improvement between group 2 and 3. 11 patients (24%) discontinued the treatment, 1 for adverse effect and 10 for inefficacy, 50% of which (5 patients) were in group 1 at the suspension moment. Conclusions: In our Glm treated SpA cohort, the majority of low activity patients and higher clinical improvement were classified in optimal or supraoptimal concentration group. Overoptimal concentration drug levels do not seem to contribute to major benefit in clinical improvement. Disclosure of Interest: None declared